Analysis of Regulatory Reform Dynamics: A Comparative Study on the Ef-ficacy of the Omnibus Law Method and Legal Codification in National Regulatory Structure. - Maarif, Ihsanul (LEGAL BRIEF, 2024)
The regulation of national laws in Indonesia faces significant challenges due to overlapping rules and regulatory inflation, which hinder legal certainty and economic efficiency. To address this issue, the government has adopted two primary approaches to regulatory reform: the Omnibus Law and Legal Codification. This study aims to analyze and compare the effectiveness of both approaches in Indonesian regulatory reform. The research employs a normative legal method with comparative analysis, utilizing data gathered from legal statutes, academic journals, and official documents. The findings indicate that the Omnibus Law is effective in addressing the need for rapid reform in dynamic sectors such as investment and labor, yet it poses risks of regulatory inconsistency, potentially leading to legal uncertainty. On the other hand, legal coding offers greater stability and consistency, though its implementation is slower and less adaptable to sectors requiring swift changes. This study's implications suggest that a selective approach is necessary, strategically applying the Omnibus Law to certain sectors while maintaining Legal Codification as the foundation for a more harmonious and sustainable legal system. This research provides recommendations for policymakers to enhance regulatory harmonization and consider the technical capacity of legal authorities in implementing reforms